1986
DOI: 10.1007/bf00152711
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin: A clinical overview

Abstract: Ribavirin, a broad spectrum, non-interferon-inducing virustatic chemotherapeutic agent, demonstrates activity against a wide range of RNA and DNA viruses, including the retrovirus known to cause the acquired immune deficiency syndrome. The drug's proposed mechanism of action, as well as pharmacokinetics are discussed, and preclinical toxicity, safety and clinical efficacy studies are presented. To date, the best success has occurred in the use of ribavirin to treat respiratory syncytial virus infection in infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
51
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 64 publications
(20 reference statements)
1
51
0
Order By: Relevance
“…Other important factors affecting serum RBV concentrations are absorption, uptake of RBV from the intestine, metabolism, and excretion. Following administration of a single capsule of RBV, the mean bioavailability of RBV is reported to be up to 40%, and saturable absorption of the drug has been suggested by the fact that the peak plasma concentration does not increase proportionally with dosage (6,30). This saturable absorption of RBV has been explained by saturation of its transport by the N1 Na ϩ nucleoside transporter located in the brush border membrane in the human jejunum and intestine (30).…”
Section: Discussionmentioning
confidence: 99%
“…Other important factors affecting serum RBV concentrations are absorption, uptake of RBV from the intestine, metabolism, and excretion. Following administration of a single capsule of RBV, the mean bioavailability of RBV is reported to be up to 40%, and saturable absorption of the drug has been suggested by the fact that the peak plasma concentration does not increase proportionally with dosage (6,30). This saturable absorption of RBV has been explained by saturation of its transport by the N1 Na ϩ nucleoside transporter located in the brush border membrane in the human jejunum and intestine (30).…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that parenterally administered RD3-0028 may not reach the lung or nasal mucosa, which are the primary target areas of respiratory virus infection, in sufficient quantities. Second, another antiviral drug, ribavirin, has been successfully administered as a continuous small-particle aerosol to humans (4,11,12,26) and cotton rats (17,36) infected with RSV. Ribavirin was shown to be significantly more efficacious when it was delivered by this route than when it was given intraperitoneally (17).…”
Section: Discussionmentioning
confidence: 99%
“…Detectable NF-B activation was not observed in TLR9-transfected HEK293 cells that were efficiently stimulated by ODN 2006 (data not shown) (14). Nevertheless, ribavirin did not stimulate considerable NF-B activation in the TRL7 and TLR8 transfectants at the biologically active in vitro concentrations (1 to 5 M) or at concentrations present in patients receiving the drug (about 50 M) (3,9,12). Further studies have to evaluate if the observed effects at high concentrations indeed reflect stimulation mediated by TLR7 and TLR8.…”
mentioning
confidence: 90%